Determinant of Nurses’ Response Time in Emergency Department When Taking Care of A Patient - Dwi Yanti Rachmasari Tartila; Andri Setiya Wahyudi; Arina Qona'ah (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2020)
Introduction: : Response time is the handling speed calculated when the patients arrive at the hospital until they are treated. It is influenced by several factors according to Gibson Performance Theory. The research approach aimed to analyze individual factors including: skills, emergency training, gender, age, length of working, and education, organizational factors: rewards, and psychological factors: nurse motivation that influences the response time of the nurses in emergency departments at general hospitals in Madura. Methods: The research method used was a descriptive-analytic study with  a cross-sectional approach. The sampling technique is total sampling, which is 101 nurses. Independent variables are skills, emergency training, gender, age, length of working, education, rewards, and motivation. Dependent variable is response time. Data were collected using a questionnaire and direct observations on nurses, data were analyzed using the Multiple Regression Logistic test. Results: The results show that there was no correlation between age (p= 0.996); education (p= 0.913); length of working (p= 0.921); training (p= 0.830); skill factor (p= 0.999); and motivation factors (p= 0.471) with response time. Whereas gender (p= 0.020); and reward factor (p = 0.020) were related with response time. Conclusion: In order to improve patients’ handling procedure, hospitals should give support  to nurses, like promotion or salary. Hospitals are expected to record documentations about the number of patients according to triage category and how fast nurses handle them because it may be an evaluation for rooms.